Does the Life Story Interview Make Us Make Sense? Spontaneous and Cued Redemption and Contamination in Life Story Scenes. (March 2018) - Alea, Nicole
The life story interview directions may be subtly encouraging the narration of affective themes, like redemption and contamination. The current study thus had men and women ( N  = 121) simply recall the details of turning, low, and high points and then separately asked them to make sense of the event. This allowed for redemption and contamination to emerge either spontaneously or after being cued. Redemption was spontaneous in 75% of turning points and 50% of the low points. There were no age differences overall or gender differences in the spontaneous narration of themes. When cued, however, women were more likely than men to narrate affective themes. Frequent rehearsal of the event also predicted spontaneous narration of themes. More work needs to be done to distinguishing who, under what circumstances, and why some individuals spontaneously make sense of their life whereas others need a cue to do so.